2020
DOI: 10.1038/s41598-020-64334-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cerebral Blood Volume under Normobaric Hyperoxia in the J20-hAPP Mouse Model of Alzheimer’s Disease

Abstract: Early impairments to neurovascular coupling have been proposed to be a key pathogenic factor in the onset and progression of Alzheimer's disease (AD). Studies have shown impaired neurovascular function in several mouse models of AD, including the J20-hAPP mouse. In this study, we aimed to investigate early neurovascular changes using wild-type (WT) controls and J20-hAPP mice at 6 months of age, by measuring cerebral haemodynamics and neural activity to physiological sensory stimulations. A thinned cranial wind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…HBOT has also been shown to increase CBF and improve EEG measurements [ 34 ], global cognitive scores [ 33 , 69 ] and PET scans [ 70 ] of post-stroke and TBI patients. In the context of Alzheimer’s disease, animal studies have shown that supplementation of oxygen [ 71 , 72 ] or HBOT [ 17 , 36 ] results in improved cognitive performance [ 71 ] and enhanced cerebral blood volume [ 72 ]. Moreover, an immediate increase in CBF due to a reduction in the number of stalled capillaries led to rapid improvement in the performance of 5XFAD mice in spatial and working memory tasks [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…HBOT has also been shown to increase CBF and improve EEG measurements [ 34 ], global cognitive scores [ 33 , 69 ] and PET scans [ 70 ] of post-stroke and TBI patients. In the context of Alzheimer’s disease, animal studies have shown that supplementation of oxygen [ 71 , 72 ] or HBOT [ 17 , 36 ] results in improved cognitive performance [ 71 ] and enhanced cerebral blood volume [ 72 ]. Moreover, an immediate increase in CBF due to a reduction in the number of stalled capillaries led to rapid improvement in the performance of 5XFAD mice in spatial and working memory tasks [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed chronic imaging of the brain cortex 3-weeks post-surgery, where the thinned cranial window remained intact (Figure 1A/B), as described previously (Shabir et al, 2020; Sharp et al, 2019). We deployed a range of stimulations (2s & 16s mechanical whisker stimulations) with the mouse breathing both 100% oxygen (hyperoxia) and 21% oxygen (normoxia), in addition to recording transitions between conditions and performing a 10% hypercapnia test to test the maximum dilation of vessels.…”
Section: Resultsmentioning
confidence: 99%
“…We performed chronic imaging of the brain cortex 3-weeks post-surgery, where the thinned cranial window remained intact (Figure 1A/B), as described previously (Shabir et al, 2020;Sharp et al, 2019).…”
Section: D-optical Imaging Spectroscopy (2d-ois) Measures Brain Cortical Haemodynamics Through a Thinned Cranial Windowmentioning
confidence: 99%
“…Still, imaging of the intracerebral vasculature technically challenging, requiring a surgically-created cranial window. Imaging the cerebral vessels is now possible for several weeks [ 23 25 ], with greater imaging depth achieved by 3‐photon fluorescence microscopy [ 26 ] and long wavelength reflectance confocal microscopy [ 27 ]. Despite such improvements in vivo imaging, most rodent studies of cerebral vessels remain histological.…”
Section: Models and Tools For Studying Cerebrovascular Developmentmentioning
confidence: 99%